Environmental and geotechnical suitability of recycling waste materials from plasterboard manufacturing. Issue 4 (April 2020) - Imteaz, Monzur Alam; Arulrajah, Arul; Maghool, Farshid
This paper presents the geotechnical and environmental suitability of recycling gypsum-based waste material produced from plasterboard manufacturing. Most of the current plasterboard manufacturing industries are dumping these wastes to landfills. Among the major impediments to recycling such waste are environmental concerns around using such recycled material, as well as proper and suitable places to use it. To investigate these, such a waste from an Australian plasterboard manufacturing company was collected and a series of geotechnical properties were tested to evaluate the materials' suitability for any engineering construction. It was found that the tested gypsum-based plasterboard materials are suitable to use as road subgrade, pipe bedding and pipe backfill material. To ascertain the environmental safety of using such material in regards to manual handling as well as contaminants' leaching into the surrounding environment, materials were thoroughly tested for more than a hundred different contaminants. Tests were conducted to evaluate both the contaminants' concentrations in the sample as well as the leaching behaviour of those contaminants. It was found that concentrations of the tested contaminants were either below the individual detection limit or the safe limit defined by the local regulatory authority.